2021
DOI: 10.1016/j.ultsonch.2021.105496
|View full text |Cite
|
Sign up to set email alerts
|

Improved modification of clinoptilolite with silver using ultrasonic radiation

Abstract: The modification of natural clinoptilolite with silver ions using ultrasound has been investigated in the current work. The modification process was performed using clinoptilolite of different fractions (0–3.0 mm) over the temperature range of 25–55 °C, ultrasonic power range of 8.0–12.5 W and AgNO 3 concentration range of 0.01–0.1 M. The zeolite modification was performed in the presence of sonication and mechanical stirring in separate runs for comparison. Fundamental analysis demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…However, in the 5 wt.% CLN/TPU nanofiber structure (Figure 3b), calcium (Ca), aluminum (Al), silicon (Si) atoms were found to be present in addition to carbon atoms. 58 This result is a proof of the presence of CLN in the structure.…”
Section: Morphological Analysis Of Cln/tpu Nanofibrous Scaffoldsmentioning
confidence: 53%
See 1 more Smart Citation
“…However, in the 5 wt.% CLN/TPU nanofiber structure (Figure 3b), calcium (Ca), aluminum (Al), silicon (Si) atoms were found to be present in addition to carbon atoms. 58 This result is a proof of the presence of CLN in the structure.…”
Section: Morphological Analysis Of Cln/tpu Nanofibrous Scaffoldsmentioning
confidence: 53%
“…It is seen that the pure TPU nanofiber structure is predominantly carbon (C) and nitrogen (N) elements (Figure 3a). However, in the 5 wt.% CLN/TPU nanofiber structure (Figure 3b), calcium (Ca), aluminum (Al), silicon (Si) atoms were found to be present in addition to carbon atoms 58 . This result is a proof of the presence of CLN in the structure.…”
Section: Resultsmentioning
confidence: 78%
“…The preparation of metal-containing zeolites is usually carried out by treating the zeolite powder in an aqueous solution of the corresponding salt, recently it has been shown that the use of ultrasound ensures desorption of air from clinoptilolite particles and accelerates the diffusion of ions and subsequent ion exchange [41].…”
Section: Preparation Of Ag- Cu- and Zn-forms Of Hcrmentioning
confidence: 99%
“…The medical utility of clinoptilolite results from its physicochemical properties that makes it suitable for medical use 16–18 . Clinoptilolite is strongly hygrophilic, possesses a unique ability for reversible cation exchange and a high adsorption capacity for diverse biomolecules 15–24 . Because of the resulting potential detoxifying effects, clinoptilolite‐based products have been proposed in many medical applications 16,18,23,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 , 18 Clinoptilolite is strongly hygrophilic, possesses a unique ability for reversible cation exchange and a high adsorption capacity for diverse biomolecules. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Because of the resulting potential detoxifying effects, clinoptilolite‐based products have been proposed in many medical applications. 16 , 18 , 23 , 25 , 26 PCT is currently marketed for oral use aimed at preventing the absorption of toxins, heavy metals and dietary cholesterol.…”
Section: Introductionmentioning
confidence: 99%